APPLICATION OF THE QUANTUM LEARNING MODEL ASSISTED BY GEOGEBRA TO SUPPORT STUDENT’S CONCEPT UNDERSTANDING ABILITY - Mursyida Mursyida; Tria Gustiningsi; Rohman Rohman (Program Studi PGSD Universitas Flores, 2024)
Understanding concepts is very important in learning mathematics because the material in mathematics learning is interconnected between one material and another. To provide understanding of concepts, student-centered learning is needed. One student-centered learning model is the quantum learning model assisted by geogebra to visualize the material provided with the aim of supporting students' understanding of concepts. The aim of this research is to describe students' ability to understand mathematical concepts after applying the geogebra-assisted quantum learning model to cube and block material. This type of research is descriptive quantitative with a posttest only research design. The subjects in this research were students in class VIII.3 of SMP Ikhlasiyah Palembang. Data collection techniques use tests of ability to understand mathematical concepts and observation of teacher and student activities to see the application of the quantum learning model. The test results show that students' ability to understand mathematical concepts is in the good category with an average score of 80.02 which is measured based on indicators of understanding mathematical concepts and from observing teacher and student activities with an average teacher activity score of 93.05%. and 94.38% of student activity shows that the application of the quantum learning model is implemented very well in the learning process.